2020
DOI: 10.1108/aeat-02-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Propulsive modelling for JT9D-3, JT15D-4C and TF-30 turbofan engines using particle swarm optimization

Abstract: Purpose The purpose of this paper is to create high-accuracy thrust modelling for cruise flight using particle swarm optimization (PSO) algorithm. Design/methodology/approach In this study, using PSO, new thrust models with high accuracy for the cruise flight stages of Pratt & Whitney JT9D-3, JT15D-4C and TF-30 engines were create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Namely, the next position of each bird/particle in the flock is found by adding the velocity vector to its current position. In this way, the algorithm tries to reach the optimum by constantly updating the position of the particles in the flock (Engelbrecht, 2007; Shi, 2001; Oruc and Baklacioglu, 2020b; Oruc et al , 2020). One of the biggest disadvantages of PSO is that it is very much affected by parameter change.…”
Section: Cuckoo Search Algorithmmentioning
confidence: 99%
“…Namely, the next position of each bird/particle in the flock is found by adding the velocity vector to its current position. In this way, the algorithm tries to reach the optimum by constantly updating the position of the particles in the flock (Engelbrecht, 2007; Shi, 2001; Oruc and Baklacioglu, 2020b; Oruc et al , 2020). One of the biggest disadvantages of PSO is that it is very much affected by parameter change.…”
Section: Cuckoo Search Algorithmmentioning
confidence: 99%
“…Zhou and Zhang presented a study report on engine thrust estimation using an ensemble of improved wavelet extreme learning machines to satisfy the conditions of direct thrust control [10]. In addition, Oruc and Bakircioglu used a particle swarm optimization algorithm to model JT9D engine thrust; in this study, the investigators found high-accuracy thrust values during cruise flights [11]. A study was proposed to investigate the application of artificial neural networks in accurately predicting aircraft thrust by leveraging the capability of ANNs to learn from large datasets [12].…”
Section: Introductionmentioning
confidence: 99%
“…Performance calculations of turbojet engines are well-known, but accurate calculations require detailed information about the components (Mattingly, 2002; Cohen et al , 1995; Walsh and Fletcher, 1998; Reffold, 1995; Kurzke, 1995). Some researchers used regression methods for modeling thrust and fuel flow consumption (Baklacioglu, 2015a, 2015b, 2016, 2017, 2021; Piskin et al , 2019; Oruc and Baklacioglu, 2020a, 2020b, 2021; Oruc et al , 2020) without going internal component details. There are also many optimization studies performed at on-design conditions.…”
Section: Introductionmentioning
confidence: 99%